In vitro antibacterial effects of photodynamic therapy against Enterococcus faecalis in root canals of deciduous teeth - Meimei Li; WenChee Wong; Huacui Xiong; Ke Chen (BMC, 2022)
Abstract Objective This study aimed at evaluating the in vitro antibacterial efficacy of photodynamic therapy (PDT) on planktonic E. faecalis and its biofilm in the root canal of infected deciduous teeth. Methods Forty root canals of maxillary deciduous anterior teeth were enlarged up to #35 K-file and inoculated with E. faecalis for 21 days. The root canals were randomly assigned into four groups (n = 10): The normal saline group (control), 1% NaClO group, PDT group, and the 1% NaClO + PDT group. Paper point samples were obtained at baseline (S1) and after treatment (S2). The colony-forming units (CFU) were counted, and the bacterial growth rate calculated. From each subgroup, 5 samples were randomly selected after treatment and a scanning laser confocal microscope (CLSM) used to determine the distribution of dead / living bacteria on the biofilm surface of each subgroup. A scanning electron microscope (SEM) was used to observe bacterial morphologies in the root canal walls of the remaining 5 samples in each subgroup. The Kruskal-Wallis test and Dunn test with boferroni adjustment were used to analyze the effect of the different treatment techniques on the E. faecalis in root canals. Results Compared to the saline group, PDT significantly reduced bacterial counts in the root canal (p < 0.05). The CFU counts were lowest (p < 0.05) in the 1% NaClO and in 1% NaClO + PDT groups. The rate of bacterial death on the surface of the biofilm in the PDT group was significantly increased after treatment (p < 0.05), and the rate of bacterial death was highest in 1%NaClO group and 1%NaClO + PDT group (p < 0.05). Conclusion PDT has an antibacterial activity against E. faecalis in the root canal of deciduous teeth. Its activity against planktonic E. faecalis is better than the activity on the intact biofilm. The antibacterial activity of PDT on E. faecalis in root canals of deciduous teeth is lower compared to that of 1% NaClO.